Factors that Influence Cecal Intubation Rate in Unsedated Patients during Colonoscopy - Suharjo B Cahyono; Putut Bayupurnama; Neneng Ratnasari; Catharina Triwikatmani; Fahmi Indrarti; Sutanto Maduseno; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: Successful cecal intubation is a primary quality indicator in colonoscopies and the mostimportant factor in detecting abnormal lesion in the colon. There are many factors that influence cecal intubationrate during colonoscopy procedure. The aim of this study is to evaluate the factors that influence cecal intubationrate in unsedated patients during colonoscopy. Method: A retrospective study of colonoscopy performed at Sardjito General Hospital, Jogjakarta, from January 2012 to August 2013. Age, sex, bowel preparation, indication for colonoscopy, colonoscopist, andreasons of incomplete colonoscopy from 564 colonoscopy reports were recorded and analysed. Results: Overall successful cecal intubation rate was 408 (72.34%). Causes of incomplete colonoscopywere patients discomfort or pain 41.66%, looping/redundant 28.85%, poor bowel preparation 18.59%, fixation/adhesion 6.41%, and bleeding risk 4.49%. Female was more unsuccessful in cecal intubation than male (31.50%vs. 24.05%; p = 0.048). The successful cecal intubation rates for gastroenterologists compared to gastroenterology(GI) fellows were 77.92% vs. 49.55%; p 0.001, and poor bowel preparation was more difficult to reach cecalthan good preparation (57.58% vs. 23.69%; p 0.001). Multivariate logistic regression analysis demonstratedthat female and poor bowel preparation were independently associated with lower cecal intubation rate, andgastroenterologists were independently associated less unsuccessful to reach cecal. Conclusion: The overall successful cecal intubation rate was still below the set standard. Several identifiedfactors that may predict lower of cecal intubation rate: the skill and experience of colonoscopists (GI fellows),poor bowel preparation and female.Keywords: cecal intubation rate, colonoscopy, unsedated colonoscopy